Peran Lingkungan Kerja Fisik dan Non-Fisik dalam Meningkatkan Kualitas Pelayanan Hotel - Muttaqin, Fatkhu Rijal; Yuliamir, Henry (Mahesa Research Center, 2025)
This article aims to analyze the influence of work environment and service quality on customer satisfaction in the hospitality industry. The focus of the study is how work environment factors, both physical and non-physical aspects, and service quality contribute to the level of customer satisfaction. The theoretical approach uses concepts from human resource management and service quality management. Data were collected through a survey of 316 hotel customer respondents and analyzed using multiple linear regression. The results of the study indicate that the work environment has a positive and significant influence on customer satisfaction, where a conducive work environment improves employee performance, which has an impact on a better customer experience. In addition, service quality also plays an important role in creating customer satisfaction, especially in terms of reliability, responsiveness, assurance, empathy, and adequate hotel facilities. However, the RÂ² value of 32.6% indicates that there are other factors that have not been studied, such as price, promotion, customer loyalty, and hotel brand image, which also affect customer satisfaction. This study concludes that improving customer satisfaction in the hospitality industry needs to be done comprehensively by considering various aspects that affect the guest's stay experience.